Legal Vacuum in Notary Office Management: The Urgency of Effective Administration and Technological Integration - Suwardiyati, Rumi; Rustam, Riky (Pustaka Peradaban, 2024)
This article delineates the urgency of regulatory reform in notary office management in Indonesia. Clear and structured regulations on the conduct of notary office management are crucial to providing solutions and legal foundations for various cases stemming from poor notary office management. It also accommodates technological advancements, ensures legal certainty, and enhances the efficiency and integrity of notarial services. The research method employed is normative legal research with a legislative and conceptual approach. This study reveals that notary office management in Indonesia still faces significant legal vacuum, particularly in regulating the process and control of deed-making. This condition can lead to practical issues such as losing deed minutes and discrepancies in the repertory, potentially harming notaries and the public. Moreover, adaptations to technologies such as electronic storage and signatures are inadequately regulated, threatening legal certainty and the integrity of notarial services. This article emphasizes the urgent need for legislative steps to fill these legal vacuum, maintain the relevance of notarial practices in the current digital era, and safeguard the interests of the public and the professionalism of notaries in Indonesia. Artikel ini menguraikan urgensi pembaruan regulasi dalam manajemen kantor notaris di Indonesia. Pengaturan yang lebih jelas dan terstruktur mengenai tata laksana manajemen kantor notaris menjadi sangat penting untuk memberi solusi dan dasar hukum atas berbagai kasus akibat buruknya manajemen kantor notaris, serta mengakomodasi perkembangan teknologi, memastikan kepastian hukum, serta meningkatkan efisiensi dan integritas layanan notaris. Metode penelitian yang digunakan adalah penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual. Kajian ini mengungkapkan bahwa manajemen kantor notaris di Indonesia masih mengalami kekosongan hukum yang signifikan, terutama dalam pengaturan proses dan pengendalian pembuatan akta. Keadaan ini dapat menimbulkan berbagai masalah praktis seperti hilangnya minuta akta dan ketidaksesuaian repertorium, yang berpotensi merugikan notaris dan masyarakat. Selain itu, adaptasi terhadap teknologi seperti penyimpanan dan tanda tangan elektronik juga belum diatur secara memadai, mengancam kepastian hukum dan integritas layanan notaris. Artikel ini menegaskan perlunya langkah legislatif mendesak untuk mengisi kekosongan hukum ini, menjaga relevansi praktik notaris dalam era digital saat ini, dan melindungi kepentingan publik serta profesionalisme notaris di Indonesia.